Linguistic Features of Women's Speech Used by Men in Characters of Pride and Prejudice and Zombies (2016) Movie - Merry Rullyanti; Kezy Claudia Dohona (UNIVED Press, 2018)
This thesis examines the linguistic features of women’s speech used by men in characters from 2016 British-American comedy and horror movie directed by Burr Steers and written by Seth Grahame-Smith and Jane Austen entitled Pride and Prejudice and Zombies. The objectives of this research can be further detailed as the following; (1) to find the linguistic features of women’s speech used by men in characters Pride and Prejudice and Zombies (2016) movie, (2) to find the functions of the linguistic features of women’s speech used by men in characters Pride and Prejudice and Zombies (2016) movie and (3) to find the kind of social manners which became the background for the men to use linguistic features of women’s speech in Pride and Prejudice and Zombies (2016) movie. With descriptive qualitative as the methodology, the researcher divide activity into three stages: first analyze linguistic features of women’s speech using theory from Lakoff (2004). Second, analyze the function of linguistic features of women’s speech using theory by Holmes (2001). Third, analyze social manners using the theory by Hoppe (2000). After the researcher analyzed data that is collected from sentence, phrase and word used by men characters in Pride and Prejudice and Zombies (20016) movie, the researcher conclude that the dominant kind of linguistic features of women’s speech used by men characters is hypercorrect grammar. And the function that dominantly used is function to strengthen (booster devices). And the dominant social manners which became the background for men to use linguistic features of women’s speech is men were dominant. Keywords: Characters of Pride and Prejudice and Zombies (2016), Linguistic Features, Women’s Speech.